A new species and new record of Polycystididae (Rhabdocoela: Kalyptorhynchia) from China - Zhong, Lin-Hong; Hu, Xiao-Zhou; Lin, Yi-Tao; Feng, Wei-Tao; Zhuang, Jie-Yi; Zhang, Yu; Wang, An-Tai (Zootaxa, 2018)
One new species and one newly recorded species of Polycystididae from China, Paulodora sinensis n. sp. and Polycystis ali Schockaert, 1982, were described based on comprehensive morphological and molecular analyses. In Paulodora sinensis n. sp., the stylet is double-walled and is composed of a funnel-shaped proximal part and a spiral distal part, while the outer stylet forms a minor fold proximally. In Polycystis ali Schockaert, 1982, the stylet is also double-walled with a funnel-shaped proximal part. However, the collar-shaped distal part is partially concave and forms a jagged edge. The concatenated 18S rDNA and 28S rDNA phylogenetic analysis supports the establishment of the new species. Besides, based on the morphology of stylet, we have made detailed categorization among the recorded species within these two genera.